Ørlandet- a study of environment, livelihood and people - Drug Issue in Ørland, Norway - Perera, M.O; Adhikari, S; Lemma, S; Daskon, C; Kanyerere, T (My University, 2003)
Drugs are mood-altering substances. By that we mean any substances that changes how people feel. These mood altering substances some are legal others are not. But they are all drugs and they can be used or abused by different people for different purposes. Norway has continued to see an increase in drug activity, coupled with an increase in the amount of drugs seized various police sections in the country that send such drugs to Oslo for testing. The problem is that the different stakeholders have different perceptions about drug the situation of drug issues which may degenerate into a problem. Therefore, the main objective of this study was to explore and understand perspectives from various people in order to highlight some of the drug related issues in Ørland Commune. Both qualitative and quantitative methods were used to collect primary data. Data collection tools included in-depth interviews with key informants and questionnaire survey. The results show that people working on drug issues said that there is drug problem in Ørland and according to them the parents have been saying that there is no drug problem in the area. The parents in general were reported to have been seeing no link between drinking alcohol and taking drugs while some of the key informants strongly believed that drinking alcohol especially during parties influence young adults to starting taking alcohol. In general, respondents gave different views regarding drug issues in terms of cause, effects and trend of the drug situation in the area. Strategies and future effectiveness of these strategies varied among the respondents. Increased activities on drug abuse awareness campaign in schools should be strengthened and simultaneously, effective awareness campaign strategies about drug issues need to be consolidated among the public in the area. In short, the study has shown that the community and the professionals have different perceptions/understandings about the drug issue ranging from its definition and the magnitude in terms of effects. Therefore, it is suggested in this paper that focus groups discussions with various sections of the community should be carried out in future. Such focus group discussions should not be limited to the professionals only but should also include young adults in schools and the different parents. This will not only give in-depth opinions from various groups but will also offset the possible biases they may come from the people working on the seemingly drug problem in the area.